ETNIS MARITIM DAN PERMASALAHANNYA - Susilowati, Endang (Fakultas Ilmu Budaya Universitas Diponegoro, 2012)
As a maritime country with vast territorial waters and abundant marine resources, Indonesia, a country with diverse ethnics and peculiarities, has a chance to become a great nation. Its natural and human resources are the basis capital to build the nation abreast with other nations in the world. Indonesia was once also known as a victorious maritime country with strong influence to the neighboring countries. Hence, it is an ironic that the maritime ethnic as the â€œguardian of the seaâ€ has to live in backwardness, deterioration, social and economic adversity, and even social and cultural decline. Support and aid both from the government and the people with commitment toward the advancement of this maritime ethnic are greatly needed. Forcing the maritime ethnic like Suku Bajo or â€œthe Sea Peopleâ€ to stay away from the sea is a futile act. In fact, it will only lead to prolonged conflict. Conversely, involving them in such a program of preserving the sea and its biota is not something that is impossible, even though it is also not easy. Along with recent changes and demands, the â€œSea Peopleâ€ or Suku Bajo eventually has to live more open and have the ability to interact with modern life.